Effect of smoothing on impact variables in soccer kicking - Gonzalez, A.; Knudson, D. (ISBS Proceedings Archive (Michigan), 2019)
This technical note examined the effect of smoothing on calculation on several impact effectiveness variables in soccer kicking. A skilled male soccer player performed 10 maximum effort place kicks with a regulation soccer ball. Two-dimensional foot and ball motion were recorded by high-speed (210 Hz) for the 0.4 seconds around impact. Kinematic data were smoothed either through impact or using a separation and five-point linear interpolation technique (Knudson, 2005). Smoothing protocol had a significant effect on three of five impact effectiveness variables (e, foot-to-ball speed ratio, VFpre). Smoothing protocol did not affect VBpost and effective striking mass. The results supported previous studies reporting distortions of velocities near impact in striking objects, however these distortions inconsistently affected more complex impact parameters. More research is needed on smoothing techniques for impact kinematic variables, particularly parameters utilizing both pre- and post-impact velocity values.